POLA KOMUNIKASI MANAJEMEN KONFLIK: STUDI FENOMENOLOGI PADA POLISI HUTAN DI CAGAR BIOSFER CIBODAS - Winarni Winarni; Iriana Bakti; Herlina Agustin; Dandi Supriadi (Forestry Study Program University Of Mataram, 2023)
The current reality is showing that the communities surrounding Cibodas Biosphere Reserve (CBC) are still doing horrible things, as evidenced by the fact that they are still taking the resources from the forest or illegally entering the area. In this case, the Forest Police (Polhut) who have responsibility for maintaining forest security, need to act to minimize disturbances in the forest area. This study aims to obtain an overview of Polhut’s communication patterns in dealing with disturbances at the Gunung Gede Pangrango National Park (TNGGP) as the core area of ​​the CBR. This study used a qualitative method through a phenomenological approach with the communication effectiveness theory. The information-gathering was conducted through an in-depth interview with two Polhut TNGGP officers who have been experienced for more than ten years in their duties. The information was processed according to the communication methods and theories. The results showed that the communication pattern conducted by the Polhut to the communities used persuasive interpersonal communication and group communication. Polhut realized that they must be close to the communities so that they can invite them to act a role in protecting forest resources. However, the communication has not been effective because there are still some obstacles to the communities and some of the supporting factors for the effectiveness of communication have not been fulfilled.